American Trappist Monasteries and the Changing Spiritual Landscape. Issue 1 (1st January 2019) - Larsen, Thomas Barclay
Abstract : Spiritual landscapes arise from a dynamic relationship of spiritual beliefs, ritual practices, and embodied encounters in place. They can contain multiple spiritual and non‐spiritual elements that change over time. This paper offers an appreciation of the diverse, overlapping, and ambivalent meanings emerging from Trappist monasteries in the United States. With origins tracing back to eleventh‐century France, Trappist monasteries are Roman Catholic intentional communities belonging to the Order of Cistercians of the Strict Observance. Attempts to establish monasteries in the American scene began around the turn of the nineteenth century. Contemplation, a receptive state of interior spiritual silence, represents one significant component of Trappist spirituality. Like other aspects of the spiritual landscape, contemplation has been reprioritized as Trappist monks and nuns confront situations like political conflict, changes in monastic leadership, and economic problems. These places continue to address challenges and possibilities for reinvention as they become open to shifting social contexts.